2013
DOI: 10.1073/pnas.1307903110
|View full text |Cite
|
Sign up to set email alerts
|

Male infanticide leads to social monogamy in primates

Abstract: Although common in birds, social monogamy, or pair-living, is rare among mammals because internal gestation and lactation in mammals makes it advantageous for males to seek additional mating opportunities. A number of hypotheses have been proposed to explain the evolution of social monogamy among mammals: as a male mate-guarding strategy, because of the benefits of biparental care, or as a defense against infanticidal males. However, comparative analyses have been unable to resolve the root causes of monogamy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
290
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(309 citation statements)
references
References 51 publications
(61 reference statements)
5
290
0
Order By: Relevance
“…These studies on the evolution of social monogamy analysed the correlated evolution of social monogamy with the traits 'male care', 'grouping structure of females' and 'infanticide risk' within primates [44] and mammals [22]. Opie et al [44] concluded that male infanticide is the most compelling explanation for the appearance of monogamy, a conclusion that may warrant further examination given that their results show similar support for a relationship to biparental care and female ranges [90]. By contrast, Lukas & Clutton-Brock [22] suggest that social monogamy evolved where males were unable to defend multiple females and conclude that its evolution was not associated with a high risk of male infanticide.…”
Section: Discussion (A) Genetic Monogamy In Azara's Owl Monkeysmentioning
confidence: 99%
“…These studies on the evolution of social monogamy analysed the correlated evolution of social monogamy with the traits 'male care', 'grouping structure of females' and 'infanticide risk' within primates [44] and mammals [22]. Opie et al [44] concluded that male infanticide is the most compelling explanation for the appearance of monogamy, a conclusion that may warrant further examination given that their results show similar support for a relationship to biparental care and female ranges [90]. By contrast, Lukas & Clutton-Brock [22] suggest that social monogamy evolved where males were unable to defend multiple females and conclude that its evolution was not associated with a high risk of male infanticide.…”
Section: Discussion (A) Genetic Monogamy In Azara's Owl Monkeysmentioning
confidence: 99%
“…A lesbian strategy to exclude the intrusion in the household of a new potentially infanticidal male might have produced strong fitness benefits on the female side. Recent studies show that female counterstrategies to avoid male infanticide in humans have been powerful in determining the adaptive value of a trait (de Waal and Gavrilets 2013;Lukas and Clutton Brock 2013;Opie et al 2013). All of the above causes might have significantly contributed to balance past HS females' lack of erotic attraction to males, increasing their fecundity compared with the present day, to possibly match the average heterosexual fecundity.…”
Section: Fecundity Of Female Hsmentioning
confidence: 99%
“…The considerable cognitive requirements of life in complex societies have resulted in many primate species having larger and more expensive brains [70], with all that this implies in connectivity. The human immersed in evolution has historically transferred the cost of learning the complexity of nature, and there is ample evidence.…”
Section: The Future In the Past? Ancient Civilizationsmentioning
confidence: 99%